STUDI AB INITIO KOMPLEKS BESI(III) DAN LIGAN N-BENZOIL-N-FENILTIOUREA - Admin APERTI (Aliansi Perguruan Tinggi Badan Usaha Milik Negara (APERTI BUMN), 2018)
N-benzoyl-N’-phenylthiourea (C14H12N2OS) has been synthesized and have potential application due to their coordination behavior toward transitional metal and also their biological activity. Iron metal was considered as one of the candidates to form complex compounds with the ligand. This study aims to examine the stability of the Iron and N-benzoyl-N’-phenylthiourea complex compound. The calculation was run under Unrestricted-Hartree-Fock method with STO-3G basis set. The higher level basis set, such as 6-31G was used to determine the energy analysis and the properties of the complex. The calculation shows that a complex structure was formed by iron(III) and the ligan through bonds with S and O atoms. On the otherway, iron(III) complex with the ligand via N atoms was not formed. It might be explained by the presence of steric hindrance in the complex.